SOCIO-CULTURAL ATHROPOLOGY OF VIETNAMESE LABOUR EXPORTED TO SOUTHEAST ASIAN COUNTRIES - Phan Thi H6ng Xuan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
Vietnam is evaluated as the nation of young population with the high rate of abor age, making up about 63% of its total population (by the end of 2006 there were 43.3 million labors, in which 22.5 % were trained workers and 5% were managing staff). However, the rate of unemployment is quite high, therefore, employment is an urgent and long-term problem. To solve this problem, it is important to develop local business and production, but also the labor export to neighbor countries and the world should be taken into account.Among Southeast Asian nations, Malaysia considered as a potential market for labor export, because it is available for unskilled workers. It needs about 1 million of foreign workers per year to fill the lacking of its local labor for the strategy of turning Malaysia into a developed industrial nation towards the year of 2020. To carry out the targets of labor export policy, besides the responsibility of concerned agencies and authorities, it is necessary to require the contribution by scientists, including Anthropology. Hopefully, the applied research of anthropology could contribute to the improvement of Vietnamese labor export to Malaysia market, and limit the risks of cultural problems particularly between Vietnamese laborers and local ones in Malaysia which is an Islamic multi-ethnic country.